Telemedicine and collaborative health information systems = Telemedizin und Kollaborative Gesundheitsinformationssysteme - Prokosch, Hans-Ulrich; Ganslandt, Thomas; Ückert, Frank (Information technology, 2009)
In this paper two major tasks of health telematics are identified: telemedicine to support the physicians and collaborative health information systems additionally incorporating the patient. In the field of telemedicine, exemplary scenarios of teleconsultation/teletherapy but also the creation of joint electronic patient records by several healthcare providers are described in detail and analysed. Those are teleradiology, telepathology, and telesurgery. On the other side, collaborative health information systems provide several means to actively incorporate the empowered patient in the care process. We illustrate the approach of sharing a patient's electronic medical record with the patient and distinguish it from alternative approaches, such as email communications between patients and doctors or patient empowerment through web-based information services. For all such applications, recent trends in research and implementation are analysed and the technological as well as legal requirements are discussed.
Gesehen am 20.06.2018